k-times attribute-based authentication scheme using direct anonymous attestation - Xin LIU; Qiuliang XU; Bin ZHANG; Bo ZHANG (Tongxin xuebao)
s: At present, the main drawbacks of existing k-times attribute-based authentication (abbreviated to k-TABA) schemes and related attribute-based authentication schemes are that the computation cost of the authentication process depends on the size of the access formula and none of these schemes considers the problems of member revocation and attribute update. A new k-TABA scheme was constructed based on the building blocks of direct anonymous attestation, set membership proof and ciphertext-policy attribute-based encryption. Moreover, in order to reduce user's calculation as much as possible, the underlying attribute-based encryption scheme was modified, and then the main decryption operations were outsourced by using the key binding technique of Green et al. The new scheme can be deployed on a trusted platform and support expressive authentication policies. In addition, it also satisfies several ideal properties, such as registration process verifiability, member revocation, attribute update, and so on. The significant performance advantage of the new scheme is that the computation overhead of the user in the authentication phase is constant.